Organelle interactions compartmentalize hepatic fatty acid trafficking and metabolism - Charles P. Najt; Santosh Adhikari; Timothy D. Heden; Wenqi Cui; Erica R. Gansemer; Adam J. Rauckhorst; Todd W. Markowski; LeeAnn Higgins; Evan W. Kerr; Matthew D. Boyum; Jonas Alvarez; Sophia Brunko; et al. (Cell Reports, 2023)
Summary: Organelle interactions play a significant role in compartmentalizing metabolism and signaling. Lipid droplets (LDs) interact with numerous organelles, including mitochondria, which is largely assumed to facilitate lipid transfer and catabolism. However, quantitative proteomics of hepatic peridroplet mitochondria (PDM) and cytosolic mitochondria (CM) reveals that CM are enriched in proteins comprising various oxidative metabolism pathways, whereas PDM are enriched in proteins involved in lipid anabolism. Isotope tracing and super-resolution imaging confirms that fatty acids (FAs) are selectively trafficked to and oxidized in CM during fasting. In contrast, PDM facilitate FA esterification and LD expansion in nutrient-replete medium. Additionally, mitochondrion-associated membranes (MAM) around PDM and CM differ in their proteomes and ability to support distinct lipid metabolic pathways. We conclude that CM and CM-MAM support lipid catabolic pathways, whereas PDM and PDM-MAM allow hepatocytes to efficiently store excess lipids in LDs to prevent lipotoxicity.